The Process Individuation of the Main Character in I Tonya Movie : An Application of Jung's Psychoanalysis - Rosalina Tumengga; Rahmawati Azi; Fina Amalia Masri (ELITE: Journal of English Language and Literature, 2023)
I, Tonya movie tells the story of Tonya Harding, an American female figure skater, from a young age Tonya was faced with her mother's strict upbringing, which made Tonya grow up with a tomboyish and stubborn attitude. This study aims to show the process of individuation that occurs in Tonya so that Tonya can achieve the self-archetype. The objective of this study is to analyze the process of individuation of the main Character Tonya Harding in I, Tonya movie. This study applies the theory by Carl Gustaf Jung. This research uses descriptive qualitative research. Data collection was carried out through four steps: watching, screenshots, note-taking, data analysis, and identifying data. The results of this study indicate that the film I Tonya shows three personas, four shadows, four animus, and oneself, before reaching the self-archetype through the Individualization process, in the film it is shown that the process of individuation occurs by eliminating the causes for the emergence of various archetypes to achieve self-archetype. In this case, Tonya can be seen that she was able to go through the process of individuation with many obstacles leading to the self archetype where she was able to control the persona, animus, shadow, and self.